PENGARUH KESESUAIAN KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL BAGIAN ADMINISTRASI PADA SEKOLAH MENENGAH ATAS NEGERI KOTA MALANG - -, Mulyono (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
AAbstract: Objectives to beachieved in this study was to determine how much influence the suitability of competence and motivation to work either simultaneousl yor partially on the performance of civil servants in the administration of the state high school Malang, as well asto determine which variable has the most dominant influence on the performance civil administration in the state high school Malang. Hypothesis testing showed that the competence and motivation have a significant effecteit her simultaneousl yor partially on the performance of civil servants in the administration of the state high school Malang. Employe ecompetence in the field of the dominant influence of work on the civil service performance administration in uppermedium school District of Malang. Keywords: Competence, Motivation and Employee Performance